ANALISIS PENERAPAN PERHITUNGAN, PENYETORAN DAN PELAPORAN PAJAK PERTAMBAHAN NILAI (PPN) PADA PT. ARKSTARINDO ARTHA MAKMUR - Rati Naila Romana; Timbul Simangunsong; Saprudin Saprudin (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2023)
This study aims to determine whether the application of the calculation, deposit and reporting of Value Added Tax (VAT) at PT. Arkstarindo Artha Makmur by adjusting Tax Law No. 42 of 2009. Data collection methods used are Observation Studies, Interview Studies, and Documentation Studies. The data analysis method used is descriptive qualitative and quantitative analysis. The results of the research show that the implementation, calculation and reporting of VAT by PT. Arkstarindo Artha Makmur cannot be said to be effective and efficient due to several inhibiting factors in the collection of VAT on Taxable Goods and Services. The company has issued an electronic Tax Invoice, performed calculations from the Tax Imposition Basis, deposited and reported Periodic VAT SPT. Company. Application of VAT calculation, deposit and reporting by PT. Arkstarindo Artha Makmur has not been effective due to differences in implementation between consumers and companies.